1993
DOI: 10.1192/pb.17.8.478
|View full text |Cite
|
Sign up to set email alerts
|

Who is watching them? A study of the interpretation of the observation policy in a mental health unit

Abstract: This project confirmed the existence of a high preva lence of thyroid disorders among people with Down's syndrome. Fourteen out of the 69 subjects (20%) had hypothyroidism, and a further seven (10%) had subclinical hypothyroidism, while there was one definite and one sub-clinical hyperthyroidism. A sex differ ence was noted, with 12of the 25 females (48%) and 9 of the 44 males (20%) having clinical or sub-clinical hypothyroidism, while the two cases of hyperthy roidism were male. Thyroid disorder was sufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
4
0
2
Order By: Relevance
“…Aus Sicht der Pflegenden werden Überwachungen auch öfter als notwendig und demzufolge ohne rechtfertigende Grundlage angeordnet, was auch mit Umsetzungsschwierigkeiten aufgrund begrenzter Ressourcen verbunden ist [35]. Nach Hodgson et al [38] sollten Pflegende an dem Entscheidungsprozess beteiligt sein und Ärzte und Pflegende am besten gemeinsam die Entscheidung für die Anordnung und die Beendigung einer Überwachung treffen. Zu vergleichbaren Ergebnissen kommen auch Langenbach et al [31].…”
Section: Praxis Der üBerwachungssituationenunclassified
See 1 more Smart Citation
“…Aus Sicht der Pflegenden werden Überwachungen auch öfter als notwendig und demzufolge ohne rechtfertigende Grundlage angeordnet, was auch mit Umsetzungsschwierigkeiten aufgrund begrenzter Ressourcen verbunden ist [35]. Nach Hodgson et al [38] sollten Pflegende an dem Entscheidungsprozess beteiligt sein und Ärzte und Pflegende am besten gemeinsam die Entscheidung für die Anordnung und die Beendigung einer Überwachung treffen. Zu vergleichbaren Ergebnissen kommen auch Langenbach et al [31].…”
Section: Praxis Der üBerwachungssituationenunclassified
“…Ethisch und fachlich muss die Frage gestellt werden, ob eine einzelne Berufsgruppe mit der Entscheidung über die Einschränkung von Persönlichkeitsrechten alleingelassen werden darf. Nach der vorliegenden Literatur [25,31,33,38,51] scheint ein multifokaler Blickwinkel, gestützt durch standardisierte Assessmentinstrumente, zu den besten klinischen Entscheidungen zu führen. Bei einer konsequenten partizipativen Entscheidungsfindung führen ärztliche Vertretungssituationen voraussichtlich nicht zu unnötig langen Überwachungsmaßnahmen.…”
Section: Interventionsebeneunclassified
“…2000); There is little agreement between authorities on what nurses should do during observation procedure, although under certain circumstances it can be therapeutic (Blythe & Pearlmutter 1983, Reid & Long 1993, Duffy 1995, Vrale & Steen 2005, Bowers & Simpson 2007); Nurses find observation procedure stressful and patients dislike it because it is oppressive and intrusive (Phillips et al. 1977, Reid & Long 1993); The decision to use observation procedure is supposed to be based upon assessment of risk, but this is an inexact science and is poorly performed (Hodgson et al. 1993).…”
Section: Literature Reviewsmentioning
confidence: 99%
“…The decision to use observation procedure is supposed to be based upon assessment of risk, but this is an inexact science and is poorly performed (Hodgson et al. 1993).…”
Section: Literature Reviewsmentioning
confidence: 99%
“…However, this author also stated that the authority to terminate the observations was less clear with most referring to a decision by a psychiatrist and little has changed today. Hodgson et al . (1993) reported that the medical staff stated that they were more involved in the decision to initiate and terminate than other disciplines and this was supported by Childs et al .’s (1994) study.…”
Section: Literature Review On Special Observations and Assessment Of mentioning
confidence: 99%